Stress biomarkers in individuals with fibromyalgia syndrome: a systematic review with meta-analysis - Beiner, Eva; Lucas, Victoria; Reichert, Julian; Buhai, Diana-Victoria; Jesinghaus, Meike; Vock, Stephanie; Drusko, Armin; Baumeister, David; Eich, Wolfgang; Friederich, Hans-Christoph; Tesarz, Jonas (Pain, 2023)
Evidence suggests an involvement of hypothalamic-pituitary-adrenal (HPA) axis dysregulation in the development and maintenance of fibromyalgia syndrome (FMS). However, studies on the stress response via the HPA-axis in individuals with FMS show conflicting results. To better understand the relationship between FMS and HPA-axis dysregulation, we (1) systematically summarized the current level of evidence on HPA biomarkers in individuals with FMS compared with individuals without and (2) evaluated whether FMS is associated with a specific pattern of HPA dysregulation. The main outcome measures were cortisol, adrenocorticotropic hormone (ACTH), corticotropin-releasing hormone (CRH), epinephrine, and norepinephrine. A systematic search of MEDLINE, EMBASE, and PsychMed yielded 47 studies eligible for meta-analysis, including 1465 individuals with FMS and 1192 FMS-free controls. No main effect of FMS was found on altered levels of blood cortisol, ACTH, CRH, and epinephrine. Compared with controls, salivary and urinary cortisol levels were decreased in individuals with FMS, whereas blood levels of norepinephrine were increased. However, heterogeneity of data was high with significant evidence for publication bias. Overall, the data are compatible with association of FMS with adrenocortical hypofunction in the presence of increased sympathetic tone. However, the data are partially contradictory, so it must be assumed that the data are highly dependent on the respective study designs, patient samples, and analytical methods and do not necessarily demonstrate an abnormal HPA-axis function in FMS.
Gesehen am 14.08.2023